IMPLEMENTASI TEKNIK KRIPTOGRAFI RSA UNTUK PENGAMANAN DATA PENGIRIMAN SMS - Ainafatul Nur Muslikah; Hardiana Riski Riswanto; Khamaida Safinah; Khadijah Fahmi Hayati Holle (Jurnal Ilmiah Informatika, 2020)
Message sending is one activity that is often used by everyone. However, security in this message delivery system needs to be wary of spying or message piracy during the process of sending messages. Surely someone who sent the message does not know if someone's personal message has been stolen. With this initiative builds a security message using cryptographic RSA algorithm where the message sender or recipient of the message can send the message safely without being known to the message hijacker or spy. Cryptography that uses the RSA algorithm to secure messages. This RSA algorithm message will be decrypted with the public key and to encrypt the message. This application was built on the Android platform because the dominant person has an Android smartphone with a system that runs the length of the message character does not affect the speed at the time of sending the message to the recipient, and there is no limit on the length of the message character during the encryption process so that any length of the massage character can be encrypted well.